1995
DOI: 10.2214/ajr.165.4.7676971
|View full text |Cite
|
Sign up to set email alerts
|

Can CT distinguish hypersensitivity pneumonitis from idiopathic pulmonary fibrosis?

Abstract: OBJECTIVE. The clinical management of patients with idiopathic pulmonary fibrosis differs markedly from that of patients with hypersensitivity pneumonitis. However, the two diseases often cannot be differentiated on clinical grounds. The purpose of this study was to establish whether CT can be used to make the distinction.MATERIALS AND METHODS. Thirty-six patients with idiopathic pulmonary fibrosis and 27 patients with hypersensitivity pneumonitis were studied. All diagnoses were confirmed or supported by open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
8

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(107 citation statements)
references
References 20 publications
2
97
0
8
Order By: Relevance
“…(17,18) In patients with fibrosing lung disease and having been exposed to HP-provoking antigens, a clinical diagnosis can be accepted, provided that the CT context is appropriate and the BAL cytology reveals lymphocytosis. (19) Fibrosing sarcoidosis (stage IV)…”
Section: Clinical and Histopathological Correlationsmentioning
confidence: 99%
“…(17,18) In patients with fibrosing lung disease and having been exposed to HP-provoking antigens, a clinical diagnosis can be accepted, provided that the CT context is appropriate and the BAL cytology reveals lymphocytosis. (19) Fibrosing sarcoidosis (stage IV)…”
Section: Clinical and Histopathological Correlationsmentioning
confidence: 99%
“…Since the diagnosis of IPF depends upon the expertise of the pathologist and radiologist, it is important that the clinician knows the diagnostic accuracy of thoracic HRCT and of lung biopsy in UIP. Various studies have calculated the accuracy of thoracic HRCT in fibrotic lung diseases [5][6][7], evaluated interobserver agreement for the diagnosis of different thoracic HRCT patterns (e.g. ground-glass and reticular pattern) [8,9] in patients with biopsy-proven nonspecific interstitial pneumonia (NSIP) or UIP [3], or in different forms of interstitial lung disease [10,11].…”
mentioning
confidence: 99%
“…Lynch et al reported that patients with IPF were more likely to have honeycombing and peripheral or lower lung zone predominance of the disease, and less likely to have micronodules, than were patients with CHP (9). They concluded that CT can be used to distinguish IPF from CHP in most but not all cases and lung biopsy should still be considered the golden standard (9). The present patient had fibrosis situated predominantly in the lower lobe, but fibrosis was also found in the upper and middle lung zones.…”
Section: Discussionmentioning
confidence: 61%